Kajian Budaya Organisasi Dalam Upaya Peningkatan Kinerja Pegawai Di Kalbis Institute - Windayanti Windayanti; Ignatius Ario Sumbogo; Nikolas Ivan Waskita Adiyasa (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
This study aims to analyze the process of forming organizational culture at the Kalbis Institute, as well as providing advice and input on the application of work culture in improving employee performance at the Kalbis Institute. This study uses a qualitative approach with a qualitative descriptive design format through in-depth interviews and in-depth observation (participant-observers) that will be conducted to research informants. Data validity and data credibility are tested using triangulation techniques. The conclusion of this study is the application of organizational culture and employee performance at Kalbis Institute is good enough.